Nexus between agricultural challenges, farming practices, and on-farm losses of selected arable crop farmers in Nigeria: a valuation constellation approach to advancing sustainable food systems - Abulude, Ifeoluwa (Frontiers in Sustainable Food Systems, 2025)
IntroductionFood loss remains a critical barrier to the sustainable transformation of global food systems, especially in the Global South, where systemic inefficiencies and data gaps persist. Despite increasing attention to food loss, less than 35% of global studies focus on losses at the primary production stage, with most research centred in the Global North. This geographical and methodological imbalance limits understanding of the complex, context-specific drivers of food loss in developing regions. This study explores how agricultural challenges influence farmers’ valuation processes and practices, and how these practices may contribute to on-farm losses offering insights within the specific context studies rather than generalisations for all of Nigeria, a country facing recurrent food insecurity and malnutrition. Using a valuation constellation perspective, conceptualising food systems as dynamic networks of interconnected actors, actions, and resources, the research explores food loss as a socially and structurally mediated phenomenon rather than a linear or isolated issue.MethodsFocus Group Discussion (FGD) were held with purposively selected farmers, facilitated by local extension agents, to gather nuanced insights into how farmers assign value and prioritise their farming practices.ResultsFindings reveal that pests and diseases are predominant challenges leading to on-farm losses among arable crop farmers. Although pests and diseases are prominent, they are embedded within a broader constellation of factors, including knowledge gaps, economic limitations, and weak institutional support. These interconnected challenges contribute to both pre- and post-harvest losses, undermining food availability and worsening hunger.DiscussionThe study emphasises the need for co-created, farmer-led strategies that address the constellation of social, material, and institutional dynamics shaping on-farm decision-making. It advocates for participatory valuation processes in policy development to ensure that farmers’ voices and rationales are structurally integrated into food system reforms. By reframing food loss through the lens of valuation constellation, this research offers a pathway towards more equitable and sustainable food system transformations.